Cultura escolar e educação no contexto da Ditadura: Feira de Santana (1968-1974) - Almeida, Aritana Lima de (2017)
The present work for the purpose, some paths covered by Brazilian education during the part of the period of greater rigidity of the civil-military regime and the way in which the ideals of conservation of the order established by dictatorship and its economic interests were reflected in teaching and culture school in the city of Feira de Santana. The analysis began in 1968, when Institutional Act No. 5 (AI-5) entered into force - when the civil-military dictatorship became more difficult, when surveillance, censorship and repression no longer existed. were veiled, but clear and cruel, and ended in 1974, as the year in which the so-called "economic miracle" ended, with an oil crisis. During the period under study, new regulations were introduced for basic and higher education, reflecting education and conservation and authoritarian state, making clear in their purposes that they aimed at building a liberal economic program and a passive and uncritical society. As legislation, education and integration of education through a critical, reflective and transformative education. The work was carried out from a case study at the Feirense Municipal Gymnasium Joselito Amorim school. The school was created in 1963, during the administration of the mayor Francisco Pinto, with the name of Municipal Gymnasium of Feira de Santana and it underwent a first hearing of the dictatorial regime soon in the following year, in 1964 with a dismissal of the mayor and appointment of Joselito Amorim to take charge, which started the construction of a new school building and points to the name of Joselito Amorim Municipal Gymnasium. The school became, therefore, a space of political conflicts, not which, through the teaching, an educated ideal of society was disputed for subjects to be formed. Oral sources, interviews with former students of the school, and photos of the city during the period studied were sent. In the first moment of the work, ruptures and continuities in education from the 1960s onwards are discussed, considering the influences exerted by the authoritarian State that was established in Brazil after 1964. In order to consolidate its ideals of development, homeland and nation, education was put under the control and surveillance of the security organs and had their curricula reformulated at all levels of education, becoming increasingly uncritical and technical, to provide more effective workforce for a developing industry. In-hand of the City of Feira de Santana during the 1960s and 1970s, addressing local politics, in line with the national political context and its influence on education movements in the city. Finally, they are addressed as memories of the subjects who experienced the education in the Municipal Gym Joselito Amorim during the period cut in the research. The memories brought by them are extremely important for an understanding of school everyday and the political elements that permeated the school culture without the end of the 1960s and the first time of the 1970s in the city of Feira de Santana.